Decolonising global health evaluation: Synthesis from a scoping review. - Ichhya Pant; Sonal Khosla; Jasmine Tenpa Lama; Vidhya Shanker; Mohammed AlKhaldi; Aisha El-Basuoni; Beth Michel; Khalil Bitar; Ifeanyi McWilliams Nsofor (PLOS Global Public Health)
As decolonisation awareness and activism amplifies in the mainstream masses and within academic realms across a variety of fields, the time is right to converge parallel movements to decolonise the fields of global health and evaluation by restructuring relations of dependency and domination reified through the "foreign gaze"1 or "white gaze." We conducted a review of relevant records with the following inclusion criteria-they define or advocate for the decolonisation of global health evaluation or explicate methods, policies or interventions to decolonise global health evaluation published by advocates of the decolonisation movement from both fields. These records were derived following a systematic article search by the lead autthor on Google, Google Scholar, NewsBank, and PubMed using the following keywords: "decolonising" and "global health," "evaluation," or "global health evaluation" replicating a digital search strategy utilized by scoping reviews across a variety of topics. Because the topic of interest is nascent and still emerging, the date range was not restricted. The lead author screened abstracts retrieved from the search. In total, 57 records, ranging in publication date from 1994 to 2020, were selected and charted for this review. We reviewed these records to identify socio-ecological factors that influence the decolonisation of global health evaluation, such as decolonising minds; reorienting funders and reforming funding mechanisms; and investing in sustainable capacity exchange. In doing so, we reflected on our positionality as well as our internalisation and potential reinforcement of colonial relations in the process of reporting our results. In the context of turmoil and transition due to the COVID-19 pandemic, our scoping review offers a starting point to embark on a journey first to transform and decolonise global health evaluation and then to achieve the greater goal of equity and justice.